Stanislav Kolíbal - former uncertain anticipated - Bogner, Dieter 1942-; Budak, Adam 1966- (Koenig Books, 2019)
The first comprehensive English-language catalogue book on Stanislav Kolibal approaches his work along two parallel paths: In the first part, all in black-and-white, the artist's biographical and personal experiences are linked with their historical context and correlated with key works produced during the same period. The second part of the catalogue, which is illustrated with numerous colour plates, illuminates important artistic developmental steps and the artist's central work groups. Exhibition: Czech and Slovak Pavilion, 58th Venice Biennal, Italy (11.05.-24.11.2019)
Published on the occasion of the exhibition ... Czech and Slovak Psavilion in Venice, 58th International Art Exhibition, La Biennale di Venezia
Genaue Ausstellungsdaten ermittelt
Keywords: Kolíbal, Stanislav -- 1925-; Kolíbal, Stanislav; Bildband; Ausstellungskatalog -- 11.05.2019-24.11.2019 -- Venedig